Toxicity levels of insecticides on diamondback moth (Plutella xylostella) from Cameron Highland, Pahang, Malaysia - Ismail, Mohd Sobri (2013)
Since 1941, the diamondback moth (DBM), Plutellaxylostella is one of the major pest of crucifers grown in the Cameron Highlands, Pahang. The larvae feed on leaves tissue, leaving the vein and cause economic losses to the cabbage farmers. Recurrent used of the same types of insecticide to control DBMs has led the insect to develop resistance. When resistance developed, the farmers will use higher dosage of insecticide and make frequent application which could causes detrimental effects to environment. The study was conducted to determine toxicity levels of selected insecticides on Plutellaxylostella from Cameron Highland. The leafdipp bioassay technique was used in this evaluation. Early third instar larvae were placed on insecticide treated cabbage leaf discs. Types of insecticide tested were Takumi® (Flubendiamide), Prevathon® (Chlorantraniliprole), Steward® (Indoxacarb) and no insecticide as control. 5 concentrations for each insecticide and 3replications were conducted to obtain LC50 values by probit analysis. Parameter recorded was the rate of larval mortality. This study was arranged in Randomized Complete Block Design (RCBD). By comparing three types of insecticides, at 72 hours, Steward® has the highest toxicity level as having the lowest LC50 value which is at 86.064ng/g in which needed only small amount a.i insecticides to kill 50% of its population. Meanwhile, Prevathon® and Takumi® have least toxicity at range 283.081ng/g and 2678.992ng/g respectively.